2015
DOI: 10.1111/njb.00851
|View full text |Cite
|
Sign up to set email alerts
|

Tragopogon turcicus sp. nov. (Asteraceae) from Turkey and its phylogenetic position

Abstract: Tragopogon turcicus Coşkunç., M.Gultepe & Makbul, a new diploid species (2n = 2x = 12), is described and illustrated from Kızıldağ National Park (Isparta), southwest Anatolia. It is morphologically similar to T. oligolepis Hartvig & Strid which is also endemic to Turkey. Diagnostic characters, description, conservation status together with micro‐ and macro‐morphological properties of achenes and pollen grains are given. A phylogenetic analysis based on nrDNA ITS sequence data indicated that T. oligolepis is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…They reported that achene characteristics were very useful for the separation and identification of different taxa within the genus. Similarly, Dogan et al (2014) and Gültepe at al. (2015b) reported that macro-and micro-morphological characters of the achenes are associated with separation of Turkish Tragopogon.…”
Section: Stem Base Without Fibrous Leaf Remains ………………mentioning
confidence: 72%
See 3 more Smart Citations
“…They reported that achene characteristics were very useful for the separation and identification of different taxa within the genus. Similarly, Dogan et al (2014) and Gültepe at al. (2015b) reported that macro-and micro-morphological characters of the achenes are associated with separation of Turkish Tragopogon.…”
Section: Stem Base Without Fibrous Leaf Remains ………………mentioning
confidence: 72%
“…), as reported by Wodehouse () and Blackmore (). Suboblate (İnceoğlu and Karamustafa , Gültepe et al ) and oblate‐spheroidal (Blackmore , Dogan et al ) have previously been reported in Tragopogon . As seen in Table , the suboblate and oblate‐spheroidal pollen grains identified in the present study were consistent with previous findings.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations